Plastic surgery emergencies principles and techniques - Bullocks, Jamal M. (Thieme Medical Publishers, Inc., 2017)
The second edition of this detailed guide to the diagnosis and treatment of common plastic surgery emergencies includes updated clinical information on the most common emergency situations. This book gives first-year plastic surgery residents the basic skills they need to progress in their training and ultimately be successful in their practice. Key Features of the Second Edition: New chapter covering sternal wounds Easy-to-follow color diagrams demonstrating key procedures and full-color photographs for rapid diagnosis Plastic Surgery Emergencies is an indispensable resource for clinicians, residents, and trainees in plastic surgery. It is also ideal for all emergency room personnel, including ER physicians, physicians' assistants, and nurse practitioners, as well as family practice physicians.